Pengaruh Budaya Organisasi dan Kepuasan Kerja Terhadap Kinerja Pegawai pada Dinas Pengendalian Penduduk dan Keluarga Berencana Kabupaten Karawang - Fajar Siddiq; Asep Jamaludin; Nandang (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of organizational culture and job satisfaction on employee performance at the Karawang Regency Population Control and Family Planning Service. In this particular investigation, a quantitative descriptive approach was used. It is estimated that the total number of employees working at the Karawang Regency DPPKB is 39 people (both population and sample). For the purpose of testing our hypothesis, we used SPSS version 25. Research findings show that organizational culture has an influence on employee performance, as indicated by a t value of 2.028 and a significance value (sig) of 0.002, lower than the acceptable threshold of 0.05. The t-calculated value of the relationship between job satisfaction and employee performance is 2.882, the t-table value is 2.028, and the significance level (sig) of 0.007 is also smaller than 0.05. Apart from that, job satisfaction has a partial influence on employee performance. This shows that organizational culture and satisfaction at work where employees operate have a positive and large influence on employee performance.